Spin-orbit torque efficiency in Ta or W/Ta-W/CoFeB junctions. (22nd October 2021) - Cha, In Ho; Lee, Min Hyeok; Kim, Gyu Won; Kim, Taehyun; Kim, Young Keun
Abstract: Efforts to improve the spin–orbit torque efficiencies in junctions consisting of nonmagnetic and ferromagnetic layers are current technological interest to construct magnetic memory and logic devices. However, most of the previous studies have relied on pure metallic elements, and thus, the outcomes were marginal. Here, we investigate the spin–orbit torque efficiencies of junctions consisting of Ta-W and CoFeB with Ta and W underlayers, focusing on the thickness and concentration of Ta-W alloy. The damping-like torque change is more significant with the W underlayer than with the Ta underlayer. We found an enhancement in damping-like torque value reaching −23% measured for a sample consisting of 4 nm thick β -phase Ta15 W85 at% layer. This value is substantially more significant than that of the junction with β -W only (−17%).